Performing Arts and BarkaNaach of Dangaura Tharus as Folk Drama - Kharel, Megh Prasad (SCHOLARS: Journal of Arts & Humanities, 2021)
This article examines different elements of folk drama in the BarkaNaach of Dangaura Tharus. It attempts to present the multiple features of the folk drama in the folk community. Based on the basic features of vernacular theatre, the study spotlights the key dramatic elements like ritual rule, context, narrative, stage and setting, characters and semiotic implication, song, dance and language as well as musical instruments and costumes in the presentation of BarkaNaach. The analysis of such drama in the light of elementary facet underlines the multiple sides of folklore as it embodies the cultural identity and value of Tharus. In doing so, I also argue that its theatrical aspects like plot and storyline are not unfamiliar to the rural farmers. Consequently, the study concludes that ritualistic performance of folk drama does not bring the unexpected happening, but it is repeated with their routinized act of cultural memory whatever performed in the past days of the ancestral force.